The Relationship between Innovation Capital, Firm Value, and Firm Risk - Arya Aji Aditya; Andi Rahmat Kaswar (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
The purpose of this study is to examine two relationships: (1) innovation capital and firm value; and (2) innovation capital and firm risk. The population of this study was all companies listed on the Indonesia Stock Exchange from 2016-2020, and the required research sample was drawn using a purposive sampling technique. Data analysis technique used multiple linear regression. The result revealed that innovation capital had a positive and statistically significant effect on firm value, but innovation capital had a negative and insignificant relationship on firm risk. Based on the analysis, it can be concluded that innovation capital has a potential factor to increase company's value, only if companies have a competitive advantage by disclosing the R&D costs and investments in their financial statements. Because of each company is unique, innovation capital is not always related to a systematic risk measurement.